Depressive Symptoms Among Wives Experiencing Domestic Violence in Indonesia: A Phenomenological Study - Agustini (Yayasan Sinergi Kawula Muda, 2026)
Domestic violence has psychological consequences for wives, yet less attention has been given to how wives in Indonesia make meaning of depressive symptoms while remaining in abusive relationships. This study explored the lived experiences, psychological dynamics, and meaning-making processes of wives who experienced depressive symptoms in the context of domestic violence. Using a qualitative phenomenological design, three wives who met the study criteria were selected through purposive sampling. Data were collected through in-depth interviews, observation, DSM-IV-TR-based depressive-symptom screening for eligibility, triangulation with significant others, and member checking. Data were analyzed using phenomenologically oriented thematic analysis through significant statements, meaning units, theme development, intracase analysis, and cross-case analysis. The findings showed that psychological violence was the most dominant form of violence. Depressive symptoms appeared through sadness, sleep disturbance, self-blame, loss of interest, emotional exhaustion, social withdrawal, helplessness, and loss of hope. These symptoms were shaped by repeated violence, limited support, economic dependence, children, and sociocultural expectations surrounding marriage and motherhood. This study contributes to a phenomenological understanding of how domestic violence may be internalized into negative meanings about the self, the marital and social environment, and the future. Support should integrate safety, legal protection, psychological care, social support, and economic empowerment.